INTEGRATION OF NI ELVIS TOOLS INTO THE EDUCATIONAL PROCESS FOR ANALYSIS OF ELECTRONICS SCHEMATICS - Kozic, Antoni; Lucun, Andzej; Tumasonis, Romanas; Macerauskas, Eugenijus; Laukhammer, Eivin (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
A receiver circuitry is provided that is primarily controlled by the NI ELVIS instrument and the LabVIEW software package. Thus, it is possible not only to control, but also to process the received signals. This article highlights how easy it is to automate receiver control and receive signal processing with NI ELVIS with LabVIEW. The article presents the practice and perspectives of using the new National Instruments LabVIEW software and NI ELVIS II hardware for teaching in the educational laboratory.